Women Leader and Political Linkage: Case Studies in Kutai Kertanegara and Bolaang Mongondow - Devy Dhian Cahyati; Desiana Rizka Fimmastuti; Norin Mustika Rahadiri Abheseka (Program Studi Sarjana (S1) Ilmu Pemerintahan, FISIP, Universitas Diponegoro, 2019)
Strengthening democracy in Indonesia provides an opportunity for women to involve informal politics. This condition is not only to show women's abilities but also to mainstream gender issues in public policy. This article explores cases of Rita Widyasari as Regent in Kutai Kartanegara and Yasti Soepredjo Mokoagow as Regent of Bolaang Mongondow to understand how they build political linkage in a local context. In this research, we use a qualitative method to gather deep information about women leaders and their linkage. The research shows that their success can not be separated from their ability to build and maintain the networks with various actors in the region, such as economic actors, civil society, and political actors. Although Rita and Yasti use a different pattern to build a local network, this research indicates that political linkage becomes one of the important points to establish women political career.